2022
DOI: 10.21070/pssh.v3i.113
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Service Quality on Customer Satisfaction at Masagung Workshop During a Pandemic Covid 19

Abstract: In the management of services during the COVID-19 pandemic, there are various kinds of assessments from service users about the Masagung Auto Body Repair workshop. The problem of service that does not satisfy customers is a separate lesson for Masagung's workshop in making considerations to evaluate the company's performance, in order to avoid a decrease in consumer interest in the future. This study aims to determine how far the level of service quality that has been provided by Masagung to customers when vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…A successful company is a company that focuses on its customers, and makes the customers as its loyal customer (Mutaqien & Prabandari, 2013), service quality is the whole customers' attitude towards a service, which is formed by a series of both successful and not successful service experiences (Susanti & Juliani, 2021). High service quality can be achieved by identifying problems in service and defining measures for service performances and outcomes as well as level of customer satisfaction (Suciptawati et al, 2019), Service quality is an abstract conception and is like to be understood because the quality of service has intangible characteristics (intangibility), varied (variability), nondurable (perishability), and production and consumption of services occur simultaneously (inseparability) (Putra & Amrial, 2021), the results showed that the quality of service has a positive and significant influence on customer satisfaction, this is in line with the research of (Maharsi et al, 2021), (Utomo et al, 2022) that customer satisfaction is influenced by the high or low quality of service. Services are well able to determine the satisfaction of consumers is the quality of services (Mahsyar & Surapati, 2020).…”
Section: The Effect Of Service Quality On Customer Satisfactionsupporting
confidence: 72%
“…A successful company is a company that focuses on its customers, and makes the customers as its loyal customer (Mutaqien & Prabandari, 2013), service quality is the whole customers' attitude towards a service, which is formed by a series of both successful and not successful service experiences (Susanti & Juliani, 2021). High service quality can be achieved by identifying problems in service and defining measures for service performances and outcomes as well as level of customer satisfaction (Suciptawati et al, 2019), Service quality is an abstract conception and is like to be understood because the quality of service has intangible characteristics (intangibility), varied (variability), nondurable (perishability), and production and consumption of services occur simultaneously (inseparability) (Putra & Amrial, 2021), the results showed that the quality of service has a positive and significant influence on customer satisfaction, this is in line with the research of (Maharsi et al, 2021), (Utomo et al, 2022) that customer satisfaction is influenced by the high or low quality of service. Services are well able to determine the satisfaction of consumers is the quality of services (Mahsyar & Surapati, 2020).…”
Section: The Effect Of Service Quality On Customer Satisfactionsupporting
confidence: 72%
“…Hasil penelitian menunjukkan bahwa kualitas pelayanan memiliki pengaruh positif dan signifikan terhadap kepuasan pelanggan. Hal ini sejalan dengan penelitian (Maharsi, Njotoprajitno, Hadianto & Wiraatmaja, 2021) dan (Utomo, Krisnanti, Zaman, Hendriawan & Manan, 2022) bahwa kepuasan konsumen dipengaruhi oleh tingkat kualitas pelayanan. Pelayanan yang baik mampu menentukan kepuasan pelanggan yaitu kualitas pelayanan (Purnomo, 2022).…”
Section: Hasil Dan Pembahasanunclassified